The Protective Effect of Anethole against Renal Ischemia/Reperfusion: The Role of the TLR2,4/MYD88/NFκB Pathway - Maged Elsayed Mohamed; Mahmoud Kandeel; Hany M. Abd El-Lateef; Hossam S. El-Beltagi; Nancy S. Younis (MDPI AG, 2022)
Background: Anethole is the principle essential oil component of anise and fennel. Renal ischemia/reperfusion (RIR) is one of the utmost imperative reasons for acute kidney injury and often associated with high mortality rate. The aim of this study is to investigate the protective effect of anethole on RIR status, exploring the involved mechanisms. Methods: RIR was accomplished by bilateral renal pedicle clamping for 45 min, after which the clamps were removed to achieve the reperfusion phase. Rats were randomized into five groups; Sham, Sham + anethole, RIR, and finally RIR + anethole (125 mg/kg or 250 mg/kg) groups. Animals were given anethole (in specified groups in doses) for 14 days before RIR. Results: RIR-experienced animals developed renal injury evidenced by diminished renal function and histopathological alteration. RIR induced severe oxidative, inflammatory, and apoptotic status within renal tissue. Pre-RIR management with anethole enhanced renal morphology and improved renal function. Anethole amplified GSH content and SOD, CAT, and GPx activities and lowered MDA. Anethole reduced gene and protein expression levels of HMGB1, TLR2, TLR4, MYD88, and NFκB. Anethole distinctly dropped TNF-α, IFN-γ, and MCP-1 levels, increased IL-10, and diminished caspase 3 and 9, reflecting its anti-inflammatory and anti-apoptotic actions. Conclusion: Anethole displayed anti-inflammatory, anti-oxidant, and anti-apoptotic actions against RIR-induced injury. Anethole exhibited renal protective actions, which could be through inhibiting the HMGB1/TLR2, 4/MYD88/NFκB pathway. These results could suggest anethole as a protective agent against RIR.